PENGARUH DIABETES MELLITUS SELF MANAGEMENT TERHADAP RESIKO KOMPLIKASI PADA PENDERITA DIABETES MELLITUS DI PUKESMAS BAJOE - Radiah Ilham; Andi Satriana; Dewi Mulfiyanti (Nusantara Hasana Journal, 2026)
Diabetes mellitus self-management refers to actions taken by an individual to independently control and manage the disease—including treatment measures and complication prevention—with the aim of reducing the incidence of vascular complications and neuropathy. This study employed a quasi-experimental design, specifically a one-group pretest-posttest design with a control group. A probability sampling method—specifically simple random sampling—was used to select 60 respondents. Data collection involved the use of the DSMQ questionnaire and an observation sheet. The Wilcoxon test results yielded a p-value of 0.009 (p < 0.05), indicating a significant influence of diabetes mellitus self-management on the risk of complications at the Bajoe Bone Community Health Center (Puskesmas). Self-management practices should be implemented among diabetes mellitus patients to prevent the risk of complications. Nurses need to provide education on diabetes mellitus self-management to enable patients to independently manage their condition and avoid the risk of diabetes-related complications.